Effect of forward head and rounded shoulder posture on hand grip strength in asymptomatic young adults: a cross-sectional study - Dalia Mohammed Mosaad (Bulletin of Faculty of Physical Therapy, 2020)
Abstract Background Forward head and rounded shoulder posture (FHRSP) is a common clinical postural misalignment. It leads to flexion posture of the spine which increases the amount of tension on the nerve roots, which inversely affects muscle strength and function of the upper extremity. So, this study was conducted to examine the effect of FHRSP on hand grip strength in asymptomatic young adults and to explore the relationship between the craniovertebral angle (CVA) and hand grip strength. Results There was no significant difference in hand grip strength between the groups (p = 0.812). There was no correlation between the CVA and right and left hand grip of the normal group (p = 0.840, 0.816 respectively), rounded shoulder posture (RSP) group (p = 0.523, 0.650 respectively), and FHRSP group (p = 0.855, 0.736 respectively). Regarding the right and left hand grip strength, there was no significant difference between the groups (p = 0.798, 0.826 respectively). The right hand grip strength was significantly higher than the left hand for all groups (p = 0.001). Conclusion This study displayed that hand grip strength was not affected by FHRSP nor RSP in asymptomatic young adults. Moreover, the degree of the CVA was not associated with an inverse effect on hand grip strength.